Evaluasi Kinerja Guru Mata Pelajaran Pendidikan Agama Kristen dalam Upaya Peningkatan Hasil Belajar dan Tercapainya Pendidikan Karakter Kristiani Bagi Peserta Didik - Tompul Tompul; Djoys Anneke Rantung; Lamhot Naibaho (Departement of Mathematics Education, 2022)
Education is a process of humanizing humans through learning in the form of actualizing the potential of students to become an ability or competency. The competencies they can have religious spiritual competence as an actualization of emotional potential (EQ), academic competence as an actualization of intellectual potential (IQ), and motor competence that is developed from sensory or physical potential. This research used qualitative research. This research is a type of research by presenting the results descriptively. Qualitative research is research that conducts renewal research. This research was carried out because there was no previous research so it was necessary to do research so that new research results were found. The results will be processed and reduction techniques will be carried out. Data can be displayed in discourse. This study can be used in analyzing the subject matter. Teacher performance has an important role in determining the quality of teaching. The quality of teaching is also influenced by the presence of good teachers in managing and handling the teaching and learning process in the classroom so as to create effective teaching. Based on the above study, the authors conclude that evaluating the performance of teachers of Christian religious education subjects is an effort to improve learning outcomes and achieve Christian character education for students. Teacher performance has an important role in determining the quality of teaching. The quality of teaching is also influenced by the presence of good teachers in managing and handling the teaching and learning process in the classroom so as to create effective teaching. The success of the teacher's performance is determined by the lesson preparation prepared by the teacher before appearing in class which also determines the effectiveness of the teaching and learning process in class.